Developing Navy Capability to Recover Forces in Chemical, Biological, and Radiological Hazard Environments - Adam C. Resnick, Steven A. Knapp (RAND Corporation, 2014)
The mission to recover amphibious forces can be complicated if ashore forces come under attack from enemy weapons, particularly chemical, biological, or radiological (CBR) weapons. If ashore forces are attacked with CBR weapons, they may become contaminated and pose a crosscontamination risk to other forces with whom they come in contact. If contaminants spread to equipment and vehicles, creating persistent hazards, these items may pose an additional crosscontamination risk. Among the potential agents that may be used in CBR weapons, persistent liquid and solid chemical agents present the greatest challenge for physical decontamination. Navy military capability will be compromised as ships’ resources are dedicated to recover contaminated ashore forces. The personnel dedicated to the recovery mission will be directed away from their other responsibilities. Areas of ships used in the recovery mission will be unusable for other activities during the recovery process, and for the duration until they are determined to be free of any potential contaminants. Navy capability will be further degraded as personnel who are injured by CBR agents become casualties, and as conventional casualties become contaminated with CBR agents that exacerbate their underlying medical conditions.